Limited Add-On Effects of Unilateral and Bilateral Transcranial Direct Current Stimulation on Visuo-Motor Grip Force Tracking Task Training Outcome in Chronic Stroke. A Randomized Controlled Trial - Taud, Benedikt; Lindenberg, Robert; Darkow, Robert; Wevers, Jasmin; Höfflin, Dorothee; Grittner, Ulrike; Meinzer, Marcus; Flöel, Agnes (Frontiers in Neurology, 2021)
Background: This randomized controlled trial investigated if uni- and bihemispheric transcranial direct current stimulation (tDCS) of the motor cortex can enhance the effects of fine motor skill training and transfer to clinical assessments of upper extremity motor function. Methods: In a randomized, double-blinded, sham-controlled trial, forty chronic stroke patients underwent five days of fine motor skill training of the paretic hand with either unilateral or bilateral (N=15/group) or placebo tDCS (N=10). Immediate and long-term (three months) effects on training outcome and motor recovery (Upper Extremity Fugl-Meyer, UE-FM, Wolf Motor Function Test, WMFT) were investigated. Results: Trained task performance significantly improved independently of tDCS in a curvilinear fashion. Anodal, but not dual tDCS resulted in a steeper learning curve on the UE-FM. Neither training alone, nor the combination of training and tDCS improved WMFT performance. Conclusions: Fine motor skill training can facilitate recovery of upper extremity function. Only minimal add-on effects of tDCS were observed. Clinical Trial Registration-URL: NCT01969097 retrospectively registered on 25/10/2013.